PENGEMBANGAN INSTRUMEN PENILAIAN UNJUK KERJA PRAKTIK PERAWATAN KULIT WAJAH BERBASIS KOMPETENSI DI UNIVERSITAS NEGERI SEMARANG - Astuti, Puji; -, Widya; Wibawanto, Hari; Khumaedi, Muhammad (Journal of Research and Educational Research Evaluation, 2015)
Penelitian ini dilatarbelakangi oleh kenyataan belum adanya instrumen penilaian perawatan kulit wajah yang baku, belum diuji validitas dan reliabilitas. Instrumen penilaian praktik yang digunakan oleh dosen pengampu mata kuliah perawatan kulit wajah masih bersifat holistic/menyeluruh atau belum terstruktur. Penelitian ini merupakan penelitian pengembangan instrumen. Uji validitas isi menggunakan rata-rata hasil penilaian dan perhitungan reliabilitas para ahli menggunakan anova satu jalur. Untuk mengetahui hasil validitas konstruk dan reliabilitas secara empirik yaitu menggunakan analisis faktor pendekatan exploratory dan alpha (?) cronbach. Hasil validitas isi pengembangan instrumen penilaian unjuk kerja praktik perawatan kulit wajah menurut para ahli masuk pada kategori sangat baik dan hasil perhitungan reliabilitas menunjukkan bahwa tidak terdapat perbedaan signifikan antara ke-lima ahli dalam menilai isi instrumen. Pengujian reliabilitas pada koefisien Alpha Cronbach pada uji coba 2 memiliki tingkat reliabilitas yang lebih tinggi. Berdasarkan hasil penelitian berupa instrumen penilaian yang valid dan reliabel maka disarankan kepada seluruh dosen pengampu pada Prodi Pendidikan Tata Rias untuk dapat menggunakan instrumen penilaian unjuk kerja praktik perawatan kulit wajah. This research is motivated by the fact the lack of standardized assessment instruments of facial skin care, has not been tested for validity and reliability. Practice assessment instruments used by lecturers in facial skin care subjects was still holistic/comprehensive or not structured. This research was the development of the instrument. The results of construct validity and empirical reliability which use exploratory factor analysis and alpha (?) cronbach. Results of the content validity of the development of performance assessment instrument of facial skin care practice according to experts belong to the category of very good and the reliability of calculation results showed that there were no significant differences between the five experts in assessing the content of the instrument. Based on these data, it can be concluded that the indicator of instrument performance assessment of facial skin care practices declared invalid. The reliability testing on the Alpha Cronbach coefficient trial 2 had a higher level of reliability. Based on the results of research in the form of assessment instruments which are valid and reliable it is recommended to all lecturers on Makeup Education Programme to be able to use an assessment instrument performance practice of facial skin care.This research is motivated by the fact the lack of standardized assessment instruments of facial skin care, has not been tested for validity and reliability. Practice assessment instruments used by lecturers in facial skin care subjects was still holistic/comprehensive or not structured. This research was the development of the instrument. The results of construct validity and empirical reliability which use exploratory factor analysis and alpha (?) cronbach. Results of the content validity of the development of performance assessment instrument of facial skin care practice according to experts belong to the category of very good and the reliability of calculation results showed that there were no significant differences between the five experts in assessing the content of the instrument. Based on these data, it can be concluded that the indicator of instrument performance assessment of facial skin care practices declared invalid. The reliability testing on the Alpha Cronbach coefficient trial 2 had a higher level of reliability. Based on the results of research in the form of assessment instruments which are valid and reliable it is recommended to all lecturers on Makeup Education Programme to be able to use an assessment instrument performance practice of facial skin care.